1971
DOI: 10.1104/pp.47.5.676
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic Leaf Movements in Biloxi Soybean and Their Relation to Flowering

Abstract: The rhythmic leaf movement of Biloxi soybean (Glycine max) and its relationship to the rhythmic flowering response were studied. The movements of fully expanded trifoliate leaves were recorded with kymographs and time lapse photography in growth chambers. A comparison between the leaf movement rhythm and the rhythmic flowering response indicates that a high degree of similarity exists between the two rhythms. A definite relationship was shown to exist between the direction of the leaf movement and the photophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1972
1972
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Therefore, very young soybean plants with unexpanded leaves can be used as the target organs to analyze the mechanism of floral induction. Previous researchers usually employed the plants with trifoliolates opened to study soybean flowering (Brest et al, 1971;Carpenter and Hamner, 1963;Coulter and Hamner, 1965;Nanda and Hamner, 1959).…”
Section: Flowering Indices Of Soybean In Different Photoperiodic Condmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, very young soybean plants with unexpanded leaves can be used as the target organs to analyze the mechanism of floral induction. Previous researchers usually employed the plants with trifoliolates opened to study soybean flowering (Brest et al, 1971;Carpenter and Hamner, 1963;Coulter and Hamner, 1965;Nanda and Hamner, 1959).…”
Section: Flowering Indices Of Soybean In Different Photoperiodic Condmentioning
confidence: 99%
“…In those studies, researchers treated soybean plants with different photoperiods or lights such as red-and far-red light when the second (Carpenter and Hamner, 1963) or third (Brest et al, 1971;Coulter and Hamner, 1965;Nanda and Hamner, 1959) trifoliolate leaf was fully expanded, and then the total number of nodes was recorded when plants flowered (Carpenter and Hamner, 1964;Coulter and Hamner, 1965;Nanda and Hamner, 1959). Their results also showed that at least three photoinductive cycles, each consisting of a short light period and a long dark period, are required to produce floral primordia (Hamner, 1940;Nanda and Hamner, 1959).…”
Section: Introductionmentioning
confidence: 99%
“…2 mean that the timing of the CO2 output maximum on NO3-medium follows that of the maximal sensitivity to a night interruption by about 3 hr, and that both respond to a change in the length of the light period in precisely the same way. These results thus confirm the conclusion tentatively (12) based only on the earlier flowering data obtained under nonskeleton photoperiods: the CO2 maximum here is an accurate indicator of the photoperiodic timing process.…”
Section: Discussionmentioning
confidence: 96%
“…Some means of following the crucial changes during induction itself would be valuable. Recognizing this problem, investigators of circadian timing in photoperiodism have used leaf movements as indicators of the effects of light and darkness, effects expressed in subsequent flowering responses (1)(2)(3). But (7), which possibly is more properly designated L. paucicostata (8), were maintained in continuous light (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation